2015
DOI: 10.1177/0363546515587082
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Comparison of an Open Repair and 3 Minimally Invasive Percutaneous Achilles Tendon Repair Techniques During a Simulated, Progressive Rehabilitation Protocol

Abstract: The reduced early elongation of open repairs suggests that patients treated with this technique may be able to progress through an earlier and/or more aggressive postoperative rehabilitation protocol with a lower risk of early irrevocable repair elongation or gapping about the repair site. However, in cases where cosmesis or wound-healing complications are of significant concern, minimally invasive percutaneous techniques provide a biomechanically reasonable alternative based on their repair strengths (cycles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
141
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(153 citation statements)
references
References 36 publications
6
141
2
4
Order By: Relevance
“…In a study by Hsu et al comparing percutaneous and open surgery techniques, complications were determined at the rate of 8.5% in all the patients who received surgery and no statistically significant difference was determined between the groups in respect of complication rates [10]. In a biomechanical evaluation of percutaneous and open surgical repair techniques, similar results were reported and it was suggested that there was a tendency for a longer postoperative rehabilitation period for clinical recovery in the percutaneous techniques compared to the open surgery techniques [11]. There are studies which have reported that there is a greater rate of sural nerve damage in the open surgical repair techniques [12].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Hsu et al comparing percutaneous and open surgery techniques, complications were determined at the rate of 8.5% in all the patients who received surgery and no statistically significant difference was determined between the groups in respect of complication rates [10]. In a biomechanical evaluation of percutaneous and open surgical repair techniques, similar results were reported and it was suggested that there was a tendency for a longer postoperative rehabilitation period for clinical recovery in the percutaneous techniques compared to the open surgery techniques [11]. There are studies which have reported that there is a greater rate of sural nerve damage in the open surgical repair techniques [12].…”
Section: Discussionmentioning
confidence: 99%
“…4,22 Prior studies have used initial linear stiffness as a surrogate measure of gapping. 10 The initial linear stiffness (N/mm) estimates the force (N) required to create a gap of 1 mm.…”
Section: Discussionmentioning
confidence: 99%
“…4 Repair strength was quantified in terms of number of cycles to failure. Significantly less early elongation was seen for open repair compared to the 3 limited open techniques, but no difference in cycles to failure was seen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations